Anther development and cytochemistry in Asphodelus aestivus (Asphodelaceae) - VARDAR, FİLİZ (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2013)
Asphodelus aestivus Brot. (Asphodelaceae) anthers were analysed to provide a detailed understanding of the events that lead to pollen grain development, accompanied by cytochemical observations at different ontogenic stages. An anther locule of A. aestivus was bordered by 4 different layers: the tapetum, the middle layer, the endothecium, and the epidermis. At the tetrad stage, secretory tapetal cells enlarged maximally, while they showed degeneration at the young microspore stage. During the course of the degeneration, vacuolisation and reduction in the volume were conspicuous. Cytochemical analysis revealed that tapetal cells presented an intense reaction with regard to protein, insoluble polysaccharides, and lipids, although the rest of the wall cells reacted weakly throughout development. The entire wall layer cells were rich in starch grains as well. The ultrastructural outcomes confirmed that orbicules were embedded within the dissolving tapetal walls. Young pollen cytoplasm was rich in mitochondria and short ER cisterns, and encircled by the intine and exine. The exine of mature pollen was of the tectate-columellate type. The intine became thicker and consisted of 2 sublayers at the sulcus. The mature pollen had the following morphological characteristics: monosulcate, heteropolar, oblate-spheroidal, widely elliptical in polar view, rhombic, and large. The cytoplasm of a mature pollen grain was filled with starch grains, insoluble polysaccharides, and proteins.
Keywords: Asphodelus aestivus; Asphodelaceae; anther development; tapetum; cytochemistry; PROGRAMMED-CELL-DEATH; TAPETAL CELLS; POLLEN GRAIN; ULTRASTRUCTURE; PHYLOGENY; ANATOMY; LILIUM